Modulating Properties of Pure ZrO2 for Structure–activity Relationships in Acid‐base Catalysis: Contribution of the Alginate Preparation Route. Issue 12 (22nd May 2017) - Wan, Elodie; Travert, Arnaud; Quignard, Françoise; Tichit, Didier; Tanchoux, Nathalie; Petitjean, Hugo
Abstract: Structure–activity relationships in heterogeneous catalysis demand the development of original preparation routes to create catalyst sets with extended surface properties. Pure zirconia is a bifunctional catalyst which shows a high versatility in acid‐base catalysis. The present work aims to synthesize a set of zirconia catalysts with various acid–base reactivities. It proposes a new route to prepare pure zirconia using sodium alginate, a low‐cost biosourced polymer. This zirconia phase is compared to samples obtained from two more conventional preparation routes, precipitation and sol‐gel. Upon calcination (500–900 °C), the alginate‐derived zirconia maintains a high specific area, which can be explained by the high dispersion of the zirconyl species in the ionogel precursor. Moreover, the three types of catalysts have distinct acid–base properties, as shown by CO2 adsorption and catalysis (methylbutynol model reaction). The alginate‐derived ZrO2 has a higher and more stable amphoteric reactivity than the phases obtained by precipitation and sol‐gel, which can be rationalized by a higher level of Lewis acid‐base pairs. Abstract : A zirconia catalyst extracted from seaweed? Not quite, but sodium alginate is a renewable marine resource that proves to be a powerful gelifying reagent to prepare precursors of ZrO2 with unusual textures. A new tool to extend the acid‐base properties of pure zirconia.